A study of the radiolysis and luminescence behavior of Dioxane-Benzene mixtures - Rojo, Enrique Aldo; Hentz, Robert R. (Elsevier BV, 1965)
Fil: Rojo, Enrique Aldo Comisión Nacional de Energía Atómica; Argentina